Psychological distress and maladaptive coping in olympic-level swimmers following postponement of the 2020 Olympic Games due to COVID-19 - Hooper, N.; Reiber, C.; Cheatham, S.; Johnson, T. (British Journal of Sports Medicine, 2021)
Background Elite-level athletes are vulnerable to psychological distress due to rigorous training and competitive schedules. Psychological screening is a preventative strategy to target athletes at risk for maladaptive coping and psychopathology; however, psychological screening is rarely implemented in elite sport environments.